ANALISIS NILAI MORAL DALAM NOVEL LASKAR PELANGI KARYA ANDREA HIRATA - Khanifah Khoerul Mar’ati; Widi Setiawati; Via Nugraha (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research is based on the fact that moral values are important, novels as written literary works must also contain moral values so that they can be used as an example, moreover the researchers themselves will be involved in the world of education, so that research on moral values can be taught more or less to students by reading literary works and looking for moral values contained in them. The problem in this study is whether there is a moral value in the novel Laskar Pelangi; then what are the moral values contained in the novel Laskar Pelangi; The purpose of this study was to analyze moral values in the novel Laskar Pelangi and describe the results of moral analysis research in the novel Laskar Pelangi. The method in this study is a descriptive method. The steps of data collection in this study are 1) Intensive reading of the novel entitled the irregulars of the rainbow 2) Recording quotes that contain moral values and analyze them. Based on the results of the study, it can be seen that there are so many moral values that the author wants to convey, including researchers finding religious or religious moral values and researchers find finding moral values related to society or social.